Let’s Pile Up Some Corpses And Pour Out A Libation – A Reconstruction Of IIIrd Millennium BC Battlefield Burial Tumulus In Ancient Mesopotamia - Paszke, Marcin Z. (Acta Archaeologica Lodziensia, 2019)
The article is devoted to the battlefield burial tumuli which are to be encountered in cuneiform texts under Sumerian SAḪAR.DU6.TAG4, DU6.SAR ĜAR, KI.GAL. It is believed that their Akkadian equivalents are bērūtum, damtum and gurunnu respectively, however it needs to be stressed, that this not certain. Since those peculiar structures have been an object of ongoing debate, the present study tries to change the trajectory of recent research and focus primarily on their physical features which have never been studied in detail before. The proposed reconstruction is based on scarce cuneiform documents and iconography known from the famous Stele of the Vultures as well as the so called ‘Standard’ of Ur. The present study deals with a battlefield barrows heaped up with the corpses of own fallen warriors in opposition to a similar structures composed of the corpses of defeated enemies, intentionally unprotected, in order to expose their bodies to outrage. The author gives an overview of the bērūtum architecture, pointing out that the structures mentioned might have been provided with a special drainage system, one comparable to the libation pipes (a-pap/a-pa4), which played an important role in the cult of the deceased in Sumerian culture.